A Statistical Experimental Study on Shrinkage of Injection-Molded Part - Rajalingam, Sokkalingam; Bono, A.; bin Sulaiman, J. (www.isaet.org, 2012)
Plastic injection molding is an important process to produce plastic parts. However, the difficulty in determining optimum process parameters setting may cause defects of the injected molded parts such as shrinkage. In this study the authors investigate the process parameters which will affect the shrinkage defect on a plastic cell phone shell component. The process parameters selected in this study are the mould temperature, injection pressure and screw rotation speed. The Design of Experimental (DOE) approach was used to investigate and identify the optimal moulding process parameters setting. The significant factors affecting the length and width of the cell phone shell were identified from ANOV A. Statistical results and analyses are used to provide better interpretation of the experiment. Confirmation run with the optimal process parameter setting found by DOE method determined that the shrinkage defect can be eliminated during mass production.